Temporal trends and long term follow-up of implantable cardioverter defibrillator therapy for secondary prevention: A 15-year single-centre experience. (1st February 2017) - Caputo, Maria Luce; Regoli, François; Conte, Giulio; Adjibodou, Boris; Svab, Stefano; Del Bufalo, Alessandro; Moccetti, Tiziano; Curti, Moreno; Klersy, Catherine; Auricchio, Angelo
Abstract: Background: The aim of this study was to determine overall and aetiology-related incidence of secondary prevention ICD implantation over the last 15 years in Canton Ticino and to assess clinical outcome according to time period of implantation. Methods and results: Consecutive patients treated by implantation of an ICD for secondary prevention from 2000 to 2015 were included in the current study and compared between 5-year cohorts (2000/2004; 2005/2009; 2010/2015). Yearly implantation rate, changing in clinical presentation over years and events during follow-up were evaluated. One-hundred fifty six patients were included. ICD implantation rate increased from 2.1 in 2000–2005 to 5.1 in 2010–2015, respectively (p 0.001). There was an increase in the proportion of non-ischaemic patients and of ventricular tachycardia (VT) as presenting rhythm. No differences in appropriate ICD interventions were observed according to aetiology, presenting arrhythmia or type of device. Reverse remodelling was observed more often in non-ischaemic patients, without any influence on the occurrence of appropriate interventions. Previous myocardial infarction (MI), atrial fibrillation (AF), NYHA class 2–3 and left ventricular ejection fraction (LVEF) < 35% were predictors of appropriate therapies during follow-up. Conclusions: Rate of implants for secondary prevention indication has almost doubled during the last 15 years. Importantly, there has been a progressive increase of non-ischaemic patients receiving an ICD, and of VT as presenting rhythm. Patients had an overall good survival and a relatively low incidence of appropriate therapies. Improvement of ejection fraction did not correlate with risk reduction of ventricular arrhythmias.